Principales problemas de sigatoka negra (Mycosphaerella fijiensis) en los últimos 2 años en la hacienda ‘‘la rabuda’’ del cantón Baba - Flores Arteaga, Luis Fernando (2020)
Bananas are one of the main export crops, as well as one of the largest generators of jobs and foreign exchange that Ecuador has. This fruit is in high demand in other continents for its flavor and high quality. There are some factors that influence banana production, such as black leaf streak disease caused by the fungus (Mycosphaerella fijiensis) that drastically attacks the foliar tissue of the crop, thus causing losses and generating a higher production cost to combat said fungus. On the farm La Rabuda, it is considered that this pathogen reduces photosynthesis and affects the normal growth of the plant. In the absence of effective control, it can reduce bunch weight by 50% and can cause 100% production losses due to poor fruit quality. In the last 2 years the farm has carried out a variety of cultural tasks and aerial fumigations that have managed to control and prevent black sigatoka, currently there is no visual evidence of damage greater than 50% in the plantation. In 2018 there was a greater infection of damage caused by this disease, which caused the quality of the fruit to decrease in size and thickness. On the other hand, in 2019 there were no problems due to additional security controls being implemented, due to the threat of the disease fusarium oxysporum race 4 that was found in Colombia.